Role of Camellia Sinensis in Polycystic Ovary Syndrome: A Systematic Review - Evi Lusiana; Fitry Dwi Asmeliana (Jurnal Ventilator, 2026)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine-metabolic disorders affecting women of reproductive age and has significant impacts on hormonal, metabolic, and reproductive functions. Conventional therapies generally focus on managing symptoms but do not comprehensively target the underlying pathogenesis of PCOS. This systematic review aimed to evaluate the potential effects of Camellia sinensis and its bioactive compounds on PCOS based on in vivo experimental studies. The review was conducted according to PRISMA 2020 guidelines using databases including PubMed, ScienceDirect, and Google Scholar. Eligible studies involved validated animal models of PCOS induced by letrozole, estradiol valerate, or similar agents, with interventions consisting of green tea extract, catechins, or epigallocatechin-3-gallate (EGCG). Risk of bias was assessed using the SYRCLE Risk of Bias tool for animal studies. Six in vivo studies met the inclusion criteria. The findings indicate that Camellia sinensis may improve hormonal imbalance, ovarian histomorphology, folliculogenesis, insulin resistance, inflammatory markers, and oxidative stress in PCOS models. One study also demonstrated enhanced metabolic and histological outcomes when EGCG was combined with vitamin D. However, the evidence remains preclinical, heterogeneous, and limited in several outcome domains. Further well-designed human studies are necessary to confirm its therapeutic potential in PCOS management.